Sustainable Rural Tourism Meaning for Community Livelihood - Dewi, Santy Paulla; Ristianti, Novia Sari (Jurnal Teknik Sipil dan Perencanaan, 2021)
The Sangiran is a national tourism strategic area as well as the most important ancient site established by UNESCO. Hence, its existence can contribute to the community livelihood which is dominated as poor. Meanwhile, having World Heritage Sites (WHS) status gives many restrictions to the local community such as restriction to soil excavation. Focusing on the agricultural sector as their main job was relatively difficult because of the physical aspect. The community chose the possible way to gain income that the job did not relate with tourism activity. Therefore, this study examines the meaning of sustainable rural tourism for community livelihood using the sustainable livelihood approach. Two rounds of Focus Group Discussions and interviews with some experts were conducted to find out issues in the development of Sangiran tourism and stakeholder perceptions. The community considered that they could not rely on the tourism sector so that they adjusted to the situation by doing another job. Indeed, the WHS status of Sangiran had not given impacts on the community; they prefer to conduct their previous activities. The development of rural tourism was not sustained; the community was still vulnerable that pointed out by their low economic capacity